Pengaruh Modal Psikologi, Iklim Psikologi dan Komitmen Terhadap Kesiapan Menghadapi Perubahan Organisasi di Era Efisiensi Anggaran Pada Dinas Pendidikan dan Kebudayaan Provinsi Maluku - Saimima, Jamdi; Rahawarin, Mohamad Arsad; Selanno, Hendry (Jurnal Ilmiah Global Education, 2025)
This study aims to analyze the application of applied statistics in processing social research data, focusing on multiple regression techniques and hypothesis testing. A quantitative approach was used to examine the relationships among variables and produce accurate, measurable findings. Data were collected from a case study in a government institution with employees as respondents. The analysis process utilized relevant statistical software to test the validity, reliability, and significance of the model. The findings indicate that the independent variables significantly influence the dependent variable at a 95% confidence level. Furthermore, the regression model is considered suitable for supporting decision-making processes. This study highlights that the application of applied statistics not only simplifies data analysis but also enhances the quality of research interpretation. Therefore, mastering statistical concepts and technical skills is essential for researchers, academics, and practitioners in the fields of social sciences and public administration.